Pengembangan Sistem Informasi Arsip Surat Berbasis Website di Desa Hegarmanah - Murdianto, Sutio; Yusman, Nova Indrayana; Furqon, Muhamad (Ma'soem University, 2024)
The new archiving system in Hegarmanah Village, in operation for one year, is currently limited to storing formal letters. It does not yet cover incoming and outgoing letters or memos, is not integrated with Gmail, and lacks alternatives for server disruptions. Web- based technology facilitates secure and efficient archive storage. This research aims to address the shortcomings of the letter archiving system in Hegarmanah Village by adding memo features, integrating the application with Gmail, and providing alternatives during server disruptions. The goal is to enhance the efficiency and effectiveness of archive management in the village, including disposition notifications and minimizing the impact of server disruptions. The system analysis and design utilize Object-Oriented Analysis and Design (OOAD) and the Rational Unified Process (RUP) model, which includes initiation, design, construction, and deployment. The system is designed using Unified Modeling Language (UML), incorporating Use Case, Class Diagram, Activity Diagram, and Sequence Diagram to create an efficient archiving system in Hegarmanah Village. Based on the research and design of the Archiving Information System in Hegarmanah Village, the archiving system now includes the management of general letters and memos, expanding its archiving functions. Letter disposition is equipped with notifications integrated with Gmail, enabling the village head and staff to receive information more quickly. Additionally, an import file feature is provided as an alternative during server disruptions, allowing data to continue functioning and be imported once the server is restored, ensuring operational continuity.